(untitled) (Nigerian Journal of Technology, 2018)
This study is on culvert performance analysis carried out in Aluu clan comprising of nine communities. A total of ten culverts located across the roads within the communities were inspected and monitored during rainy season. It entails assessing the culverts to ascertain their functionalities. Amongst all the culverts, one location was observed to be problematic because of the extent and duration of flooding after an incidence of intense rainfall in the area. From field data obtained, the Rational method was employed to determine the peak design flow as 450 ft3/s (12.74 m3/s). The hydraulic analysis was carried out using HY-8 software (in imperial units) by US Federal Highway Administraion, a powerful tool for analyzing variety of culvert shapes and configurations. From field measurements it was discovered that the existing circular culvert comprising of three barrels of 3 ft (914 mm) diameter, each has a headwater elevation of 115.72 ft (35.27 m) as compared to the roadway elevation of 115 ft (35.05 m). The existing circular culvert was redesigned as box and circular options for comparison and selection. Comparing the two redesigned options, circular and box culverts having headwater elevations of 113.06 ft (34.46 m) and 109.58 ft (33.40 m) while tail-water elevations of both is 106.17 ft (32.36 m), with respect to roadway elevation of 115 ft (35.05 m). Both design options are capable of containing the design flow without any incidence of flooding. However, box culvert has an advantage of lower headwater elevation. Also, both circular and box culverts are outlet control as depicted by culvert performance curves. We stand to gain by redesigning existing culverts observed to experience flooding during heavy storms of short durations. There is need to monitor performance of existing culverts as some were designed with limited field data resulting in under- or over- design. Keywords: Circular and Box culverts, headwater elevation, HY-8 software, Design flow, Aluu Clan, Port Harcourt.